ANALISIS YURIDIS SOSIOLOGIS TERHADAP PELAKSANAAN PERATURAN DAERAH NOMOR 8 TAHUN 2006 TENTANG LARANGAN PEREDARAN MINUMAN BERALKOHOL DAN PENGAWASANNYA DI KABUPATEN JENEPONTO - Limpo, Affandi Makmur; Patawari, Patawari (Fakultas Syariah Institut Agama Islam Negeri (IAIN) Pontianak, 2020)
The purpose of this research is to reveal the implementation of Government Regional Regulation No. 8 of 2006 on Prohibition of Alcoholic Beverages Circulation and its Supervision in Jeneponto District. It is because alcoholic beverages either modern or traditional still circulating illegally. The method of this research is empirical legal research using a sociological juridical approach. The result of this research revealed that implementation of Government Regional Regulation No. 8 of 2006 on Prohibition of Alcoholic Beverages Circulation and its Supervision in Jeneponto District was not worked because of the absence of derivative rules under it, such us technical instruction and implementing instruction, lack of supervision and law enforcement toward eatery or retail stalls outside of the special zone, the absence of measurable programs, the absence of roadmap for controlling alcoholic beverages and mild criminal sanctions.